The Effect of Acceptance and Commitment Therapy on Social anxiety and Perceived Stress in patients with Epilepsy - Sadeghnejad , Hamideh; Teimory , Saeed; Amiri , Mehdi (Shahroud Journal of Medical Sciences, 2021)
Background: Epilepsy is one of the most common neurological disorders that can cause social anxiety and perceived stress in individuals. This study aimed to investigate the effects of Acceptance and Commitment Therapy (ACT) on social anxiety and perceived stress in patients with epilepsy.Methods: It was a quasi-experimental study with pre-test and post-test design and equal control group performed on people with epilepsy under the auspices of the Khorasan Razavi epilepsy support association in 2019. Thirty patients were selected by purposive sampling method and randomly assigned to two groups (15 patients in the experimental group and 15 patients in the control group). Research tools including Conver's social anxiety questionnaire (2000) and Cohen et al.'s (1983) perceived stress questionnaire were used. Multivariate analysis of MANCOVA and ANCOVA multivariate analysis of covariance was used for data analysis.Results: The results showed that the mean of social anxiety and perceived stress in the experimental group decreased significantly compared to the control group in the post-test (Pvalue<0.05). The results of one-way analysis of covariance with pre-test control showed that there was a significant difference between the two groups in terms of social anxiety (F=65.75 and Pvalue<0.001). Moreover, there was a significant difference between patients with epilepsy in the experimental group and the control group in terms of perceived stress (F=138.56 and Pvalue<0.001).Conclusions: It can be said that the ACT can reduce social anxiety and perceived stress in patients with epilepsy.Keywords: Epilepsy, Patient, Acceptance and commitment therapy, Social anxiety, Perceived stress